Antioxidative activity of ginger and coriander in cooked patties of mackerel (Scomber Scombrus) during storage / Normah I ... [et al.] - Ismail, Normah; W, Diana; I, Norisuliana; A, Nur Azura (Faculty of Applied Sciences, 2005)
This study was carried out to determine the potential effects of ginger and coriander on reducing lipid oxidation of cooked patties of Mackerel (Scomber scombrus) during refrigerated storage. Four treatments were used consisting offish + coriander (1 %), fish + ginger (1 %), fish + ginger (0.5%) + coriander (0.5%) and fish only as a control. Lipid oxidation was evaluated based on the total lipid content, peroxide value and free fatty acid value. Samples were also sensory evaluated for rancid odor. From this study, antioxidant activity increased in the order of coriander < ginger + coriander < ginger, lipid oxidation increased in the order of coriander > ginger + coriander > ginger. From the observation for 12 days of refrigerated storage (4 °C), it was found that rancidity increased with storage period. The degree of rancid odor increased in the order of coriander > ginger + coriander > ginger.